Revolutionizing Situations of Children in Conflict with the Law: Addressing the Rights and Rehabilitation of Juvenile Offenders (Journal of Advances and Scholarly Researches in Allied Education, 2017)
One of the most critical issues in crime today is children in conflict with the law. A 'juvenile' means a kid or a girl who has not attained the age of 18 years. The Children's Act of 1960 defines a delinquent as 'a child who has submitted an offense'. In a wide sense however, juvenile delinquency isn't merely 'juvenile crime'. It grasps all and any deviations from normal youthful conduct and includes the incorrigible, the ungovernable, the habitually defiant and the individuals who desert their homes and blend with immoral people, those with behavioral problems and indulging in antisocial practices. According to Articles 37 and 40 of the Convention on the Rights of the Child (1989), children in conflict with the law have the privilege to treatment that advances their feeling of respect and worth considers their age and goes for their reintegration into society. Also, placing children in conflict with the law in a closed facility should be a measure of last resort, to be kept away from at whatever point possible. The convention prohibits the burden of capital punishment and sentences of life detainment for offenses conferred by people younger than 18.